"I want us to be a normal family": Toward an understanding of the functions of anonymity among U.S. oocyte donors and recipients. Issue 4 (2nd October 2018) - de Melo-Martín, Inmaculada; Rubin, Lisa R.; Cholst, Ina N.
Abstract: Background : Anonymity remains the more common practice in gamete donations, but legislation prohibiting anonymity with a goal of protecting donor-conceived children's right to know their genetic origins is becoming more common. However, given the dearth of research investigating the function of anonymity for donors and recipients, it is unclear whether these policies will accomplish their goals. The aim of this study was to explore experiences with anonymity among oocyte donors and recipients who participated in an anonymous donor oocyte program and to understand the ways in which anonymity functions for them.Methods : Semistructured interviews were conducted with 50 women: 28 oocyte donors and 22 recipients who were recruited from an academic center for reproductive medicine in the United States.Results : Donors and recipients view anonymity both as a mechanism to protect the interests of all parties (recipients, donors, and donor-conceived children) and as a point of conflict. Specifically, three key areas were identified where both donors and recipients saw anonymity as having an important role: relieving anxieties about family structures and obligations; protecting their interests and those of donor-conceived children (while acknowledging where interests conflict); and managing the future.Conclusion : As gamete donation increasingly moves away from the practice of anonymity, examining why anonymity matters to stakeholders will be helpful in devising strategies to successfully implement identity-release options.